Analisis Optimalisasi Pengelolaan Dana Desa untuk Kesejahteraan Masyarakat di Kecamatan Aek Bilah Kabupaten Tapanuli Selatan - Ritonga, Mirnawanti (el Buhuth: Borneo Journal of Islamic Studies, 2021)
This type of research is quantitative research. This study uses a quantitative approach in the form of financial ratio data based on time series. The data used is annual data. The data analysis technique used by the researcher is regression analysis. The population in this study was the entire community of South Tapanuli Regency. While the sample of this research is 15 villages from Aek Bilah District, South Tapanuli Regency. The sampling technique Iof this research is saturated sampling. Data collection techniques in this study used interview and documentation techniques. The results of the study show that partially there is a significant positive influence between Government Implementation, development Implementation, Community Development, Community Empowerment on Community Welfare. In contrast to the mitigationLthat has a negative effect on the welfare of the community, it means that there is no significant effect of the mitigation on the welfare of the community. Simultaneously Government Implementation, Development Implementation, Community Development, Community Empowerment, Management have an effect on Community Welfare in Aek Bilah District, South Tapanuli Regency in 2019-2021 seen from theLlarge F count of 1421,371 > FLtable 2.45 then H 0 rejected and Ha accepted. So, iit can be concluded that simultaneously Government Implementation, Development Implementation, Community Development, Community Empowerment, Management have an effect on Community Welfare.